Impact of sovereign credit ratings on emerging bond and stock market returns - Mkhonto, Zoyisile (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
The primary role of credit rating agencies is to reduce asymmetric information between the parties in a lending relationship. The three major rating agencies have received extensive criticism over the years. These rating agencies have been accused of providing inaccurate ratings which ultimately led to various financial calamities. Late rating action has also been blamed for exacerbating financial and economic cycles. Moreover, there is an argument that emerging markets are unfairly rated in comparison to developed economies. Hence, the reliability and informational value of the assessments provided by credit rating agencies is met with scepticism. Despite these criticisms, rating agencies are characterised as gatekeepers to capital and credit ratings remain essential financial market indicators. Albeit, the literature regarding the impact of sovereign credit ratings on bond and stock markets is inconclusive. This study aims to add to the body of literature and provide insights into the informational value of sovereign credit ratings in emerging markets. More specifically to estimate the relationship between various sovereign credit rating announcements, and bond and stock market returns. Also, to examine whether sovereign credit ratings have a differential impact between bond and stock markets. As well as address the question does it matter who provides the rating? Using an event study, abnormal returns surrounding rating announcements from 2009 to 2019 for 24 emerging markets were analyzed. Firstly, this study concluded that sovereign credit ratings are informative. Secondly, the degree of informativeness differs between the bond and stock markets. Thirdly, an asymmetrical impact was observed between the types of rating announcements. Lastly, that it does matter which rating agency provides the rating because each agency has a unique reputation. The findings of this research have implications on how investors and portfolio managers decide on asset allocation. Furthermore, policymakers may find our investment grade analysis of value when evaluating regulatory reform. It's recommended that future research refines the event methodology and examines country specific characteristics within each of the emerging markets.
Keywords: Rating agencies (Finance); Credit ratings; Bond market